EVALUATING THE EFFECTIVENESS OF CUPPING THERAPY IN ENHANCING MUSCULOSKELETAL RECOVERY IN ATHLETES - Dr Monika Sharma; Aksha (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Delayed onset muscle soreness (DOMS) impairs athletic performance by causing pain, stiffness, and reduced joint mobility. Cupping therapy, a traditional technique increasingly used in sports recovery, is claimed to mitigate DOMS, but robust evidence is scarce.Objective: To compare the efficacy of cupping therapy versus standard recovery methods (static stretching and ice application) in alleviating DOMS, improving joint range of motion (ROM), and enhancing athlete satisfaction.Methods: In a randomized controlled trial, 50 athletes (56% male, mean age 24.98 ± 2.48 years) with DOMS (baseline VAS ≥4) were assigned to either a cupping therapy group (10-minute dry cupping sessions, three times weekly) or a control group (15-minute static stretching and ice sessions, three times weekly) for 6 weeks. Outcomes included DOMS intensity (Visual Analog Scale, VAS), knee ROM (goniometer), and satisfaction (5-point Likert scale), assessed at baseline, week 3, and week 6. Data were analyzed using paired and independent t-tests.Results: At week 6, the cupping group showed significantly lower VAS scores (M = 3.08, SD = 1.55) than the control group (M = 5.56, SD = 1.04; t = -6.63, p < 0.001, Cohen’s d = -1.88). ROM improved significantly overall (p = 0.001, Cohen’s d = -0.50), but group differences were not assessed. Satisfaction averaged 2.86 (SD = 1.33) without group-specific analysis.Conclusion: Cupping therapy effectively reduces DOMS intensity, supporting its role in sports recovery. Larger studies with group-specific ROM and satisfaction comparisons are warranted.